Determinants of youth unemployment in Aganang Municipality, Limpopo Province - Mphela, Nkwe (Research of GSB, 2018)
Employment is one of the most significant determinants of the welfare of any nation. Any significant changes in employment (i.e. increase/decrease) will subsequently affect the wellbeing of the household. The unemployment rates in South Africa are among the highest in the world, currently standing at 25.2 per cent (i.e. by the narrow definition of unemployment) based on figures released by Statistics South Africa. Limpopo tends to have the highest proportion of rural dwellers in the South Africa, hence it is expected that socioeconomic conditions in the province are inferior to the national average; with the consequence of a high youth unemployment rate. This study seeks to find the determinants of youth unemployment in the Aganang municipality of the Limpopo province using census 2011, complemented by QLFs 2007-2010. This study used the same approach that Kyei and Gyekye followed by employing Regression, Principal, Component and Cluster analyses. Three variables, gender, training and education were categorised into twelve as independent variables. The study concluded that in the Aganang municipality, no education (that is no schooling or primary schooling) particularly for females, caused the level of Youth unemployment to rise, while a bachelor's degree and / or training, brought about a reduction in Youth unemployment.